Traumatic appendicitis is probably not real: an illustrative analysis of coincidental occurrences in nature - David N Naumann; Tom Barker (Trauma Surgery & Acute Care Open)
There have been sporadic case reports describing ‘traumatic appendicitis’ (acute appendicitis occurring following injury) for almost a hundred years. Although this might seem to be an interesting and rare diagnosis for the journal reader, both appendicitis and trauma are very common, and their occurrence together may only give the illusion of causality. Indeed, such a diagnosis may not even exist. We provide an illustration of the statistical phenomenon of coincidental occurrences in nature using a computer simulation of traumatic appendicitis in the UK population. In our simulation, there are enough cases of traumatic appendicitis every 2 years to 3 years to account for the entire global literature on the topic. We suggest that unless there is a credible pathological process reported with demonstrable causality, further case reports of traumatic appendicitis need to have robust justification.